PENGEMBANGAN LKS BERBASIS KETERAMPILAN PROSES SAINS PADA MATERI HUKUM-HUKUM DASAR KIMIA - Winny Ardhiantari; Noor Fadiawati; Nina Kadaritna (Universitas Lampung, 2015)
The research and development of students worksheets based on the science process skills on the fundamental laws of chemistry topic has been studied. This research used the method of research and development. The students woksheets which were developed had characteristics that suitable with the expected competencies, attractive to students as well as didactics, constructions, and technicals requirements have been qualified. Premilinary field testing of the students worksheets as development product was conducted at the 10th grade of SMAN 14 Bandar Lampung. Based on teachers responses about suitability of the contents, constructions, and readability aspects of the students worksheets, it were categorized in very high. Based on students responses about readability and attractiveness aspects of the students worksheets, it were also categorized in very high. The result showed that the student worksheets was proper to be used.Telah dilakukan penelitian dan pengembangan LKS berbasis keterampilan proses sains pada materi hukum-hukum dasar kimia. Penelitian ini menggunakan metode penelitian dan pengembangan (Research and Development). LKS yang dikembangkan memiliki karakteristik sesuai dengan kompetensi yang diharapkan, menarik untuk siswa serta telah memenuhi syarat didaktik, syarat teknik, dan syarat konstruksi. Uji coba lapangan awal LKS sebagai produk hasil pengembangan dilakukan di kelas X SMAN 14 Bandar Lampung. Berdasarkan hasil tanggapan guru terhadap aspek kesesuaian isi, konstruksi, dan keterbacaan, aspek tersebut dikategorikan sangat tinggi. Berdasarkan hasil tanggapan siswa terhadap aspek keterbacaan dan kemenarikan, aspek tersebut juga dikategorikan sangat tinggi. Hasil penelitian menunjukkan bahwa LKS hasil pengembangan layak untuk digunakan.Kata kunci: hukum-hukum dasar kimia, KPS, LKS